Development of scientific bases of technologies of activation of electrodes for water electrolysis - Yu. I. Kryukov; V. P. Lukovcev; E. M. Petrenko (Тонкие химические технологии, 2010)
Electrochemical activity of electrodes with different catalysts is investigated for the reactions of hydrogen and oxygen evolution. The expediency of use of the developed methods of activation of electrodes for electrolysis of water is shown.